EFFECTIVENESS AND CONTRIBUTION ANALYSIS OF LOCAL TAXES AND RETRIBUTIONS TO REGIONAL OWN-SOURCE REVENUE - Suci Nasehati Sunaningsih1; Risma Wira Bharata; Agustina Prativi Nugraheni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Regional Own Source Revenue (PAD) is the regional government's principal source ofcapital, used to fund all expenditures and reduce reliance on payments from the federaland provincial governments. The size of the natural and tourism potential controlled bythe Government of Magelang Regency should significantly contribute to the PAD ofMagelang Regency, but it does not do so in practice. The purpose of this study is toassess the effectiveness and contribution of PAD sources in Magelang Regency,specifically local taxes and retributions on PAD. Secondary data in the form of a BudgetRealization Report (LRA) for the period 2016-2020 was utilised. The effectivenessanalysis revealed that the Government of Magelang Regency can collect local taxes veryefficiently for 5 (five) years in a row, with an annual effectiveness ratio exceeding 100%.Local retribution, on the other hand, has not been properly implemented, as evidenced bythe effectiveness ratio of local retribution, which varies year to year and is included inthe Less Effective group. Local taxes contribute enough to PAD, according tocontribution analysis, with an average contribution ratio of 34% in the Fairly Goodcategory. The contribution of local retributions to PAD, on the other hand, is included inthe Very Poor category, with an average contribution ratio of roughly 6% every year